First report of a primitive neuroectodermal tumor of the bladder in a newborn - Silva Caso, Wilmer Gianfranco (2020)
Primitive neuroectodermal tumor (PNET) is part of the Ewing sarcoma family of tumors. The present case reports a primitive neuroectodermal tumor (PNET) of rare location in the bladder in a newborn. It was evaluated with prenatal ultrasound and postnatal tomography that revealed a mass in the posterior wall of the bladder. The patient underwent partial cystectomy with subsequent analysis of the surgical piece removed, the histopathological study indicated a tumor of mesenchymal origin, and immunohistochemical staining confirmed the diagnosis of PNET of the bladder. Satisfactory result and short-term follow-up.